FTIRS-based opal data of IODP Site U1537 - Hallmaier, Moritz; Gutjahr, Marcus; Lippold, Jörg; Hemming, Sidney R; Gerber, Lukas; Weber, Michael E; Eisenhauer, Anton (In: Hallmaier, M et al. (2025): Authigenic Uranium Preservation and Bottom Water Oxygenation in the Scotia Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982959, 2025)
This data is complementing the dataset from Weber et al. 2022. We used Fourier Transform Infrared Spectroscopy (FTIRS) to quantify biogenic opal to obtain information on past changes in ocean productivity. FTIRS has first been implemented successfully to reconstruct paleoproductivity changes in neighboring Sites MD07-3133 and MD07-3134 for which FTIRS derived opal has been compared against opal measured by means of 'conventional' leaching techniques (Sprenk et al., 2013). At Site U1537, 287 samples have been measured for the past 0.4 Ma and published along with details on the method in (Weber et al., 2022). Here, we added an additional 48 samples to increase the sample resolution.
Keywords: authigenic uranium; Biogenic Barium (xsBa); bottom-water oxygenation; export productivity; opal; Scotia Sea; sediment; Southern Ocean; Th; thorium normalization; Weddell Sea